Development and validation of the arabic version of the social-ecological model questionnaire for patients undergoing maintenance hemodialysis - Ayman S. Abutair; Md Mizanur Rahman; Asri Bin Said (PLoS ONE, 2025)
Background Patients undergoing maintenance hemodialysis (MHD) in Arabic-speaking regions, particularly in Palestine, face unique sociopolitical and cultural barriers affecting their care and quality of life. Existing assessment tools rarely address the multi-level determinants of support within these populations, highlighting the need for a culturally validated instrument based on the Social-Ecological Model (SEM). Objective To develop and validate an Arabic-language questionnaire grounded in the SEM to assess the multi-level (community, interpersonal, organizational, and policy) support factors influencing MHD patients in the Gaza Strip. Methods A cross-sectional study was conducted from November 2024 to February 2025 at three governmental dialysis centers in Gaza, enrolling 101 Arabic-speaking adult MHD patients through systematic random sampling. The validation process encompassed item analysis, content and face validity, and psychometric testing, including exploratory factor analysis (EFA), assessment of convergent and discriminant validity which includes average variance extracted, factor loadings, composite reliability, Cronbach’s alpha, Fornell-Larcker criterion, cross-loadings, and Heterotrait-Monotrait ratio. Results The EFA identified a four-factor structure corresponding to Community, Interpersonal, Organizational, and Policy Support, explaining 65.15% of the variance. The final validated questionnaire comprised 31 items, with the Community Support domain demonstrating the strongest psychometric properties (factor loadings: 0.821–0.923; Cronbach’s alpha = 0.972; AVE = 0.796). While Interpersonal and Organizational domains showed acceptable reliability and validity, the Policy Support domain displayed marginal construct validity. Overall, the instrument had strong content, face, convergent, and discriminant validity. Conclusion The Arabic SEM-based questionnaire is a reliable and valid tool for assessing multi-level support factors among MHD patients in Arabic-speaking contexts. It enables comprehensive evaluation for research and clinical practice. Future research should confirm its structure using confirmatory factor analysis, extend validation to diverse Arab populations, and examine temporal stability.